Negotiating Sacredness: Buddhist Iconography and Market Dynamics in Ladakh’s Thangka Trade - Bhutia, Karma Norbu (Journal of International Buddhist Studies, 2025)
Over the last few decades, artists in Ladakh have made significant changes to sacred Buddhist art, particularly in how they create thangkas. Thangkas were primarily used in religious ceremonies, but are now sold in tourist markets and monasteries. This commercialisation of thangkas raises questions about their authenticity, ritual value, and cultural continuity. This paper is based on ethnographic work conducted in the Leh district of Ladakh, India, in 2025, which integrates semi-structured interviews with artists, shop proprietors, and women conservators of the Shesrig Foundation with visual analyses of paintings and murals. The findings show that artists respond differently to commercial pressure. Rabden and Chuskit adhere closely to canonical iconometry, consecration rituals, and devotional discipline, whereas Birju and Tsewang modify imagery, pigments, and production speed to cater to the demands of tourists. Synthetic colours have replaced mainly natural, mineral-based colours, although natural materials continue to be used in conservation work and for high-value commissions. Shop owners often act as cultural mediators, educating buyers about cultural significance and the ritual placement of thangkas, and encouraging their participation. The women conservators of the Shesrig Foundation are a big change in a field that has mostly been run by men. This study demonstrates that changes in Ladakh’s thangka trade are not a story of decline, but of ongoing negotiation, where livelihood, ritual practice, and cultural continuity coexist in dynamic tension.